Polymers, positive electrode material compositions and their applications
By using multifunctional polymers in the positive electrode material of lithium-ion batteries, uniform dispersion and multi-point adsorption of the positive electrode active material are achieved, solving the problem of degradation of battery circulation performance and improving the initial efficiency and flexibility of the battery.
Patent Information
- Application Number
- JP2024555273
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-09-15
- Filing Date
- 2022-10-28
- Publication Date
- 2025-04-16
Smart Images

Figure 2025511549000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of batteries, and in particular to polymers, positive electrode material compositions, positive electrode slurries, positive electrode plates, secondary batteries, and power consuming devices. [Background technology]
[0002] Batteries are closely related to people's lives and are widely used in various small portable electronic devices. With the emergence of energy shortage and environmental pollution problems, batteries have become the core of large devices such as electric vehicles and clean energy storage devices. With the continuous development of lithium-ion batteries, the performance requirements and operating environment requirements for lithium-ion batteries are also becoming higher and higher, that is, they are required to be safe and efficient, have high capacity, high multiplication factor, and long cycle life. Compared with the conventional lithium-ion secondary battery positive electrode materials, spinel structure LiFePO4 and layer structure LiCoO2, LiFePO4 has a wider raw material supply source, lower price, no environmental pollution, and lithium iron phosphate has outstanding advantages in terms of high temperature performance and safety.
[0003] Due to the different lithium iron phosphate processes on the market, the polarity and non-polarity (or weak polarity) of the microscopic surface are different, which makes the lithium iron phosphate slurry difficult to disperse during production and gels. At the same time, some additives have appeared on the market, but these additives cannot be used universally, and it is necessary to develop corresponding additives according to the properties of the main material during production, and at the same time, it is necessary to constantly change the production line, which has a great impact on production efficiency. Summary of the Invention
[0004] The present application provides a polymer, a positive electrode material composition, a positive electrode slurry, a positive electrode plate, a secondary battery, and a power consuming device to solve the problem of poor cycle performance of a battery due to the inability of the positive electrode active material to be uniformly dispersed in the active layer.
[0005] A first aspect of the present application provides a polymer, the polymer comprising -COOR 1 , -SO3R 2 and-PO(OR 3 ) OR 4 and R 1 , R 2 , R 3 and R 4 each independently includes a first group and a second group, the first group being H and the second group being C1 to C 12 Alkyl groups, C6-C 20 Aryl groups and C5-C 20 heteroaryl groups; The solvated segment is TIFF2025511549000002.tif5083, TIFF2025511549000003.tif50153, Any one or more of the segments consisting of the unit TIFF2025511549000004.tif52130 are selected, R 5 is selected from any one of C1 to C6 alkylene groups, and 30≦a≦60, 1≦n≦10, 1≦b≦8, 0≦c≦20, and 8≦d≦60.
[0006] The anchor group and the end group in the polymer are both connected to the solvation segment by chemical bonds, and can simultaneously have the specific anchor group and solvation segment. The anchor group simultaneously has a first group and a second group, and the first group, H, is an ionizable group and can adsorb a polar group (e.g., Li2CO3, Li3PO4, etc.) in the positive electrode active material. The second group is a non-ionizable group and can adsorb a non-polar group (e.g., coated carbon) in the positive electrode active material. The anchor group contains these groups, so that it can realize an adsorption and dispersion action on the positive electrode active material. Therefore, it can realize multi-point adsorption on positive electrode active materials with strong polarity and weak polarity, and achieve the purpose of efficiently dispersing the positive electrode active material. In addition, the structure contains solvation segments, which spread in the solvent of the positive electrode slurry, causing a steric hindrance effect, further enhancing the dispersion effect, improving the dispersibility of the positive electrode active material and the conductive agent, forming a better conductive network in the positive electrode film layer, and reducing the film resistance (resistance value can be made ≦1Ω), thereby improving the initial efficiency and cycle performance of the secondary battery. In addition, since the solvation segments contain spin-flexible groups such as CO and CC, the flexibility of the plate can be improved, and problems such as the poor brittleness of thick-coated, high-voltage, and high-density plate plates, which causes the inner winding ring to crack and causes the battery to self-discharge can be solved.
[0007] In some embodiments, the molar ratio of the anchor group to the solvation segment to the end group is (1-1.5):(8-8.8):(0.2-0.5), which enhances the effect of the polymer as an additive to the positive electrode material composition.
[0008] In any embodiment of the first aspect, the second group is selected from the group consisting of C1-C6 alkyl groups and C6-C 12 aryl groups, optionally 30≦a≦40, 1≦n≦5, 4≦b≦8, 1≦c≦10, 8≦d≦20; and optionally the terminal group is C1-C 12 Alkyl groups, C1-C 12 Alkoxy groups and C6-C 20aryl groups, and more optionally, the terminal group is selected from any one or more of C1-C6 alkyl groups, C1-C6 alkoxy groups, and C6-C 12 The polymer having the second group and the terminal group reduces the viscosity of the slurry when the slurry is formed, so that the positive electrode active material is more easily dispersed in the solvent, and the dispersibility of the positive electrode active material in the solvent is more favorably improved, and the problem of the positive electrode plate coating cracking is effectively controlled.
[0009] In any embodiment of the first aspect, the molar ratio of the first group to the second group is controlled to be 2:8 to 8:2 to accommodate the dispersion requirements of positive electrode active materials of different polarities.
[0010] In any embodiment of the first aspect, the weight average molecular weight of the polymer is 500 to 20000, and optionally 1000 to 10000. A polymer having a weight average molecular weight in the above range contributes to further increasing the dispersibility of the positive electrode active material, while also contributing to controlling the viscosity of the formed positive electrode slurry, making it easier to coat, and further mitigating the problem of cracking of the positive electrode plate coating.
[0011] A second aspect of the present application provides a positive electrode material composition comprising a positive electrode active material, a conductive agent, and an additive which is any one of the polymers according to the first aspect.
[0012] By using the above polymer of the present application, it is possible to realize multi-point adsorption to the positive electrode active material of strong polarity and weak polarity, and to achieve the purpose of efficiently dispersing the positive electrode active material. In addition, the structure contains a solvation segment, which can further increase the dispersibility of the positive electrode active material and the conductive agent, and can form a better conductive network in the positive electrode film layer, and can reduce the film resistance (resistance value can be made ≦1Ω), thereby improving the initial efficiency and cycle performance of the secondary battery. In addition, since the solvation segment contains a spin-flexible group such as CO or CC, it can improve the flexibility of the electrode plate, and solve the problem of the poor brittleness of the thick-coated, high-voltage, and high-density electrode plate, which causes the inner ring of the winding to crack, resulting in self-discharge of the battery.
[0013] In any embodiment of the second aspect, the weight content of the additive in the positive electrode material composition is 0.01% to 3%, and optionally 0.2% to 0.5%. The additive within the above weight content range can not only utilize its sufficient anchor group to realize sufficient dispersion in the positive electrode active material, but also avoid the influence of the additive usage amount on the energy density of the positive electrode plate formed later, and further increase the initial efficiency and cycle maintenance rate of the secondary battery.
[0014] In any embodiment of the second aspect, the weight content of the positive electrode active material in the positive electrode material composition is 94% to 99%, and optionally the positive electrode active material includes any one or more of the group consisting of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, magnesium-rich lithium nickel cobalt manganese oxide, lithium manganese spinel, and lithium nickel manganese spinel. The positive electrode material composition of the present application is suitable for dispersing various positive electrode active materials, particularly lithium iron phosphate positive electrode active materials having different polarities.
[0015] In any embodiment of the second aspect, the D V50 The particle size is 0.8 μm to 2.5 μm. This is to avoid gelling due to aggregation of the positive electrode active material caused by a particle size that is too small, and to avoid an effect on the magnification performance caused by a particle size that is too large.
[0016] In any embodiment of the second aspect, the weight content of the conductive agent in the positive electrode material composition is 0.3% to 3%, and optionally, the conductive agent includes one or more of the group consisting of conductive carbon black, conductive graphite, metal particles, carbon nanotubes, carbon fibers, graphene, and conductive polymers, thereby increasing the conductivity of the formed positive electrode film layer as much as possible.
[0017] In any embodiment of the second aspect, the positive electrode material composition further comprises a binder, and optionally the weight content of the binder in the positive electrode material composition is 0.5% to 3%, and optionally the binder comprises one or more of the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, vinylidene fluoride-trifluorochloroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, and vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer. The caking property of the formed positive electrode active material on the current collector is increased as much as possible, and the occurrence of the cracking problem of the electrode plate is further controlled.
[0018] A third aspect of the present application provides a positive electrode slurry comprising a solvent and any one of the positive electrode material compositions according to the second aspect. The positive electrode slurry of the present application contains the additive, so that the positive electrode active material is dispersed relatively uniformly therein.
[0019] In any embodiment of the third aspect, the viscosity of the positive electrode slurry is further controlled to 4000 to 30000 mPa·s by adjusting the content of the solvent in the positive electrode slurry and adjusting the composition of the positive electrode material composition within the above range.
[0020] A fourth aspect of the present application provides a positive electrode plate including a current collector and a positive electrode film layer comprising any one of the positive electrode material compositions according to the second aspect or obtained by drying any one of the positive electrode slurries according to the third aspect. Since the positive electrode film layer of the present application comprises the positive electrode material composition or is obtained by drying the positive electrode slurry, the positive electrode active material is uniformly dispersed therein, the electrical conductivity is high, the film resistance is low, and the flexibility is improved, and the self-discharge problem of a battery including the same is effectively controlled.
[0021] A fifth aspect of the present application provides a secondary battery including any one of the positive plate described above, a separator, and a negative plate.
[0022] A sixth aspect of the present application provides a power consuming device including a secondary battery selected from the above secondary batteries, or a battery module or a battery pack.
[0023] Since the positive electrode material composition of the present application contains the above-mentioned additives, the positive electrode active material is uniformly dispersed in the formed positive electrode slurry, and the content of the positive electrode active material in the positive electrode slurry can be further increased, so that the formed positive electrode plate has a better conductive network, lower film resistance, and increased film flexibility, thereby increasing the compression density of the secondary battery, reducing self-discharge, and exhibiting excellent initial efficiency and cycle performance, and improving the safety of the power consuming device. [Brief description of the drawings]
[0024] In order to more clearly describe the technical solutions of the embodiments of the present application, the drawings that need to be used in the embodiments of the present application are briefly described below. It is obvious that the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain further drawings based on the drawings without making creative efforts.
[0025] [Figure 1] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 2] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. [Diagram 3] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Figure 4] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Diagram 5] FIG. 5 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 4. [Figure 6] 1 is a schematic diagram of a power consuming device that uses a secondary battery as a power source according to one embodiment of the present application.
[0026] In the drawing section, the drawings are not drawn to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, the embodiments of the present application will be described in more detail with reference to the drawings and examples. The detailed description of the following examples and the drawings are intended to illustratively explain the principles of the present application, but are not intended to limit the scope of the present application, i.e., the present application is not limited to the examples described.
[0028] Hereinafter, with reference to the drawings as appropriate, embodiments specifically disclosing the polymer, positive electrode material composition, positive electrode slurry, positive electrode plate, secondary battery, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of substantially the same structure may be omitted. This is to avoid unnecessary redundancy in the following description and to allow those skilled in the art to easily understand. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0029] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the boundaries of the given range are defined by the selected lower and upper limits. Such a defined range may or may not include both end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a given parameter, it is understood that ranges of 60-110 and 80-120 are also anticipated. Also, if 1 and 2 are listed as the minimum range values, and 3, 4, and 5 are listed as the maximum range values, then the ranges of 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all anticipated. In this application, unless otherwise stated, the numerical range "a-b" represents a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are recited herein, and "0-5" is simply shorthand for combinations of these numerical values. Note that when a parameter is described as an integer ≧2, this is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0030] Unless otherwise stated, all the embodiments and optional embodiments in the present application can be combined with each other to form new technical solutions.
[0031] Unless otherwise stated, all technical features and optional technical features in the present application can be combined with each other to form new technical solutions.
[0032] Unless otherwise stated, all steps in the present application may be performed in sequence or randomly, preferably in sequence. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed in sequence, or steps (b) and (a) performed in sequence. For example, when the method includes a step (c), which means that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b).
[0033] Unless otherwise stated, the terms "comprise" and "comprises" used herein may be open ended or closed ended. For example, the terms "comprise" and "comprises" may indicate that the composition may further include or include other components not listed, or may include or include only the listed components.
[0034] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions satisfy the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or both A and B are true (or exist).
[0035] [Secondary battery] A secondary battery is also called a rechargeable battery or a storage battery, and refers to a battery that can be continuously used by activating the active material by charging after the battery has been discharged.
[0036] Typically, a secondary battery includes positive and negative plates, a separator, and an electrolyte. During the charge and discharge process of the battery, active ions (e.g. lithium ions) are repeatedly inserted and removed between the positive and negative plates. The separator is placed between the positive and negative plates and mainly serves to prevent short circuits between the positive and negative plates while allowing the active ions to pass through. The electrolyte is placed between the positive and negative plates and mainly serves to conduct the active ions.
[0037] [polymer] One embodiment of the present application provides a polymer, the polymer comprising -COOR 1 , -SO3R 2 and-PO(OR 3 ) OR 4 and R 1 , R 2 , R 3 and R 4 each independently includes a first group and a second group, the first group being H and the second group being C1 to C 12 Alkyl groups, C6-C 20 Aryl groups and C5-C 20 heteroaryl groups; The solvated segment is TIFF2025511549000005.tif5284, TIFF2025511549000006.tif50151, Any one or more of the segments consisting of the unit TIFF2025511549000007.tif52130 are selected, R 5 is selected from any one of C1 to C6 alkylene groups, and 30≦a≦60, 1≦n≦10, 1≦b≦8, 0≦c≦20, and 8≦d≦60.
[0038] The anchor group and the end group in the polymer are both connected to the solvation segment by chemical bonds, and can have the specific anchor group and solvation segment at the same time, the anchor group has a first group and a second group at the same time, the first group H is an ionizable group and can adsorb polar groups (such as Li2CO3, Li3PO4, etc.) in the positive electrode active material, the second group is a non-ionizable group and can adsorb non-polar groups (such as coated carbon) in the positive electrode active material, and the anchor group contains these groups to realize the adsorption and dispersion action on the positive electrode active material, so that the multi-point adsorption on the positive electrode active material with strong polarity and weak polarity can be realized, and the purpose of efficiently dispersing the positive electrode active material can be achieved. In addition, the structure contains a solvation segment, and the solvation segment spreads in the solvent of the positive electrode slurry, causing a steric hindrance effect, which can further enhance the dispersion effect, increase the dispersibility of the positive electrode active material and the conductive agent, and more positive electrode active material can be used in the positive electrode slurry. Using this, a better conductive network is formed in the positive electrode film layer, which reduces the film resistance (resistance value can be made ≦1Ω), improving the initial efficiency and cycle performance of the secondary battery.In addition, since the solvation segment contains spin-flexible groups such as CO and CC, the flexibility of the plate is improved, and problems such as the poor brittleness of thick-coated, high-voltage, and high-density plates, which causes the inner winding ring to crack and causes the cell to self-discharge, can be solved.
[0039] In some embodiments, the molar ratio of the anchor group, the solvation segment and the terminal group is (1-1.5):(8-8.8):(0.2-0.5). When the polymer is an additive to the positive electrode material composition, the effect of the polymer is enhanced, and the electric performance of the secondary battery and the flexibility of the positive electrode plate can be adjusted by adjusting the ratio of the three within the above range. For example, when the ratio of the anchor group is increased, the dispersibility of the positive electrode active material is further improved, the resistance of the positive electrode plate is reduced, and the initial efficiency and cycle performance of the secondary battery are improved. When the ratio of the solvation segment is increased, the flexibility of the formed positive electrode plate is better, and the brittleness of the positive electrode plate is further reduced.
[0040] In some embodiments, the second group is selected from the group consisting of a C1-C6 alkyl group and a C6-C 12 aryl groups, optionally 30≦a≦40, 1≦n≦5, 4≦b≦8, 1≦c≦10, 8≦d≦20; and optionally the terminal group is C1-C 12 Alkyl groups, C1-C 12 Alkoxy groups and C6-C 20 aryl groups, and more optionally, the terminal group is selected from any one or more of C1-C6 alkyl groups, C1-C6 alkoxy groups, and C6-C 12 The polymer having the second group and the terminal group reduces the viscosity of the slurry when the slurry is formed, so that the positive electrode active material is more easily dispersed in the solvent, and the dispersibility of the positive electrode active material in the solvent is more favorably improved, and the problem of the positive electrode plate coating cracking is effectively controlled.
[0041] In some embodiments, the molar ratio of the first group to the second group is controlled to 2:8 to 8:2 to accommodate the dispersion requirements of positive electrode active materials of different polarities. For example, when the polarity of the positive electrode active material is strong (i.e., the degree of graphitization after carbon coating is small), a polymer with a high ratio of the first group is used, and when the polarity of the positive electrode active material is weak (i.e., the degree of graphitization after carbon coating is large), a polymer with a low ratio of the first group is used, thereby further enhancing the dispersion effect of the polymer on the positive electrode active material.
[0042] The above polymer is used as an additive for the positive electrode material composition mainly to promote the dispersion of the positive electrode active material, and the more anchor groups there are, the more advantageous it is for the dispersion of the positive electrode active material, but the more anchor groups there are, the larger the polymer molecules required will be, which will further affect the viscosity of the formed positive electrode slurry, so in some embodiments, the weight average molecular weight of the above polymer is 500 to 20000, and optionally 1000 to 10000. A polymer in the above weight average molecular weight range contributes to further increasing the dispersibility of the positive electrode active material, while also contributing to controlling the viscosity of the formed positive electrode slurry, making it easier to coat, and further mitigating the problem of cracking of the positive electrode plate coating.
[0043] [Positive electrode material composition] Another embodiment of the present application provides a positive electrode material composition including a positive electrode active material, a conductive agent, and an additive which is any one of the polymers described above.
[0044] By using the above polymer of the present application, it is possible to realize multi-point adsorption to the positive electrode active material of strong polarity and weak polarity, and to achieve the purpose of efficiently dispersing the positive electrode active material. In addition, the structure contains a solvation segment, which can further increase the dispersibility of the positive electrode active material and the conductive agent, and can form a better conductive network in the positive electrode film layer, and can reduce the film resistance (resistance value can be made ≦1Ω), thereby improving the initial efficiency and cycle performance of the secondary battery. In addition, since the solvation segment contains a spin-flexible group such as CO or CC, it can improve the flexibility of the electrode plate, and solve the problem of the poor brittleness of the thick-coated, high-voltage, and high-density electrode plate, which causes the inner ring of the winding to crack, resulting in self-discharge of the battery.
[0045] In some embodiments, the weight content of the additive in the positive electrode material composition is 0.01% to 3%, and optionally 0.2% to 0.5%. The additive within the above weight content range can not only utilize its sufficient anchor group to realize sufficient dispersion in the positive electrode active material, but also avoid the influence of the excessive additive usage on the energy density of the positive electrode plate formed later, and further increase the initial efficiency and cycle maintenance rate of the secondary battery.
[0046] The amount of the positive electrode active material used in the positive electrode material composition of the present application can refer to the prior art, and since the additive used enhances the dispersibility of the positive electrode active material, the content of the positive electrode active material can be increased compared to when no additive is used, but in some embodiments, the weight content of the positive electrode active material in the positive electrode material composition is 94% to 99%, and optionally, the positive electrode active material includes any one or more of the group consisting of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, magnesium-rich lithium nickel cobalt manganese oxide, lithium manganese spinel, and lithium nickel manganese spinel. The positive electrode material composition of the present application is suitable for dispersing various positive electrode active materials, particularly lithium iron phosphate positive electrode active materials having different polarities.
[0047] In some embodiments, the positive electrode active material D V50 The particle size is 0.8 μm to 2.5 μm. This is to avoid gelling due to aggregation of the positive electrode active material caused by a particle size that is too small, and to avoid an effect on the magnification performance caused by a particle size that is too large.
[0048] The content of the conductive agent in the positive electrode material composition of the present application can also refer to the prior art. In some embodiments, the weight content of the conductive agent in the positive electrode material composition is 0.3% to 3%, and optionally, the conductive agent includes one or more of the group consisting of conductive carbon black, conductive graphite, metal particles, carbon nanotubes, carbon fibers, graphene, and conductive polymers. The conductivity of the formed positive electrode film layer is increased as much as possible. As the conductive carbon black, commonly used carbon black such as Ketjen black and acetylene black can be used.
[0049] The content of the binder in the positive electrode material composition of the present application can also refer to the prior art, and in some embodiments, the positive electrode material composition further includes a binder, and optionally, the weight content of the binder in the positive electrode material composition is 0.5% to 3%, and optionally, the binder includes one or more of the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, vinylidene fluoride-trifluorochloroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, and vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer. The binding property of the formed positive electrode active material on the current collector is increased as much as possible, and the occurrence of the cracking problem of the electrode plate is further controlled.
[0050] [Positive electrode slurry] Another embodiment of the present application provides a cathode slurry comprising a solvent and any one of the cathode material compositions described above. The cathode slurry of the present application has the additives described above, so that the cathode active material is dispersed relatively uniformly therein.
[0051] In some embodiments, the viscosity of the positive electrode slurry is further controlled to 4000-30000 mPa·s by adjusting the content of the solvent in the positive electrode slurry and adjusting the composition of the positive electrode material composition within the above range. When the viscosity of the positive electrode slurry is within this range, the positive electrode slurry does not stratify, has no obvious static viscosity rebound, and does not experience sedimentation or gelation when stirred slowly. The above viscosity can be obtained by testing using the following method.
[0052] Take a 500ml beaker to take a sample from the stirring tank immediately after stirring, select a 62# rotor, set the water bath temperature to 45℃, set the speed to 12RPM, rotate the viscometer up-down button, slowly lower it, avoiding the inclusion of air bubbles, immerse the rotor into the slurry from the center position of the beaker until it sinks into the rotor groove, press the motor start key, start measuring and timing, read the relatively stable data within 3~6min, this data is the viscosity value of the measured sample.
[0053] [Positive plate] The positive electrode plate usually includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.
[0054] As an example, the positive electrode current collector has two surfaces opposing each other in the thickness direction of the positive electrode current collector, and the positive electrode film layer is provided on either one or both of the two opposing surfaces of the positive electrode current collector.
[0055] The positive electrode membrane layer includes any one of the positive electrode material compositions described above or is obtained by drying any one of the positive electrode slurries described above. The positive electrode membrane layer of the present application includes any one of the positive electrode material compositions described above or is obtained by drying the positive electrode slurry described above, so that the positive electrode active material is uniformly dispersed therein, the electrical conductivity is high, the membrane resistance is low, and the flexibility is improved, and the self-discharge problem of the battery including the same is effectively controlled.
[0056] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, the metal foil may be an aluminum foil. The composite current collector may include a polymeric material base layer and a metal layer formed on at least one surface of the polymeric material base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0057] In some embodiments, the positive electrode plate can be manufactured by the following method. The components for manufacturing the positive electrode plate described above, such as the positive electrode active material, the conductive agent, the binder, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry. The positive electrode slurry is applied to a positive electrode current collector, and after processes such as drying and cold pressing, a positive electrode plate can be obtained.
[0058] [Negative plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.
[0059] As an example, the negative electrode current collector has two surfaces opposing each other in the thickness direction of the negative electrode current collector, and the negative electrode film layer is provided on either one or both of the two opposing surfaces of the negative electrode current collector.
[0060] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, the metal foil may be a copper foil. The composite current collector may include a polymeric base layer and a metal layer formed on at least one surface of the polymeric substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0061] In some embodiments, the type of negative electrode active material may be a negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. The silicon-based material may be selected from at least one of silicon alone, silicon oxygen compound, silicon carbon composite, silicon nitrogen composite, and silicon alloy. The tin-based material may be selected from at least one of tin alone, tin oxide compound, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a negative electrode active material of a battery may be used. These negative electrode active materials may be used alone or in combination of two or more.
[0062] In some embodiments, the negative electrode membrane layer optionally further comprises a binder. As an example, the binder can be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0063] In some embodiments, the negative electrode film layer optionally further comprises a conductive agent. As an example, the conductive agent can be selected from one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0064] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).
[0065] In some embodiments, the negative electrode plate can be manufactured by the following method. The components for manufacturing the negative electrode plate described above, such as the negative electrode active material, the conductive agent, the binder, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry. The negative electrode slurry is applied to a negative electrode current collector, and after processes such as drying and cold pressing, a negative electrode plate can be obtained.
[0066] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative plates. In the present application, the type of electrolyte is not specifically limited and can be selected according to needs. For example, the electrolyte may be liquid, gel-like, or all solid.
[0067] In some embodiments, the electrolyte is a liquid and includes an electrolyte salt and a solvent.
[0068] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0069] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0070] In some embodiments, the electrolyte solution optionally further includes additives. For example, the additives may include anode film-forming additives, cathode film-forming additives, and may also include additives capable of improving specific performance of the battery, such as additives for improving the overcharge performance of the battery, and additives for improving the high-temperature or low-temperature performance of the battery.
[0071] [Separator] In some embodiments, the secondary battery further includes a separator. The present application does not particularly limit the type of the separator, and any known separator with a porous structure having good chemical stability and mechanical stability can be selected.
[0072] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single layer film or a multi-layer composite film, and is not particularly limited. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, and is not particularly limited.
[0073] In some embodiments, the positive plates, negative plates, and separators can be manufactured into an electrode assembly by a winding process or a lamination process.
[0074] In some embodiments, the secondary battery may include an exterior body that can be used to package the electrode assembly and the electrolyte.
[0075] In some embodiments, the exterior body of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior body of the secondary battery may be a soft pack, such as a bag-type soft pack, etc. The material of the soft pack may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0076] In the present application, the shape of the secondary battery is not particularly limited, and may be cylindrical, rectangular, or any other shape. For example, FIG. 1 shows a secondary battery 5 having a rectangular structure as an example.
[0077] In some embodiments, referring to FIG. 2, the exterior body may include a case 51 and a cover plate 53. The case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround the chamber to form a chamber. The case 51 has an opening communicating with the chamber, and the cover plate 53 may cover the opening to seal the chamber. The positive electrode plate, the negative electrode plate and the separator may form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the chamber. The electrolyte infiltrates the electrode assembly 52. The number of electrode assemblies 52 included in the lithium ion battery 5 may be one or more, and may be selected by those skilled in the art according to specific practical requirements.
[0078] In some embodiments, the secondary batteries can be assembled into a battery module, and the number of secondary batteries included in the battery module can be one or more, and the specific number can be selected by a person skilled in the art according to the application and capacity of the battery module.
[0079] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, the multiple secondary batteries 5 may be arranged in order along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by a fastening member.
[0080] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0081] In some embodiments, the above battery modules can be further assembled into a battery pack, and the number of battery modules included in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0082] 4 and 5 show an example of a battery pack 1. Referring to Fig. 4 and Fig. 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 provided in the battery box. The battery box may include an upper box 2 and a lower box 3, and the upper box 2 may cover the lower box 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box according to any format.
[0083] The present application further provides a power consuming device including at least one of the secondary battery, battery module, or battery pack provided by the present application. The secondary battery, battery module, or battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., secondary battery electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric cars, ships and satellites, energy storage systems, etc.
[0084] The power consumption device can be selected as a secondary battery, a battery module or a battery pack according to the needs of the usage.
[0085] 6 shows an example of a power consumption device, such as a secondary battery electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be adopted to meet the high power and high energy density requirements of the secondary battery of the power consumption device. EXAMPLES
[0086] The following examples of the present application are described. The following examples are illustrative and are merely for the purpose of interpreting the present application, and should not be understood as limiting the present application. If no specific techniques or conditions are specified in the examples, they are performed according to the techniques or conditions described in the literature in the field or according to the product specifications. If no manufacturer is specified for the reagents or equipment used, they are all conventional products that are commercially available.
[0087] The positive electrode active material is carbon-coated LiFeO4, the positive electrode active material used in Examples 1 to 50 is carbon-coated LiFeO4 corresponding to a test graphitization degree of 0.195 purchased from Hunan Yuneng, and the positive electrode active material used in Examples 51 to 53 is carbon-coated LiFeO4 corresponding to a test graphitization degree of 0.281 purchased from Jiangxi Sublimation New Material. From the graphitization degree, it can be seen that the surface polarity of the two types of materials is different.
[0088] Comparative Example 1 The positive electrode active material lithium iron phosphate, the conductive agent SP carbon black (from TIMCAL), and the binder polyvinylidene fluoride (PVDF) were mixed homogeneously in a weight ratio of 97:2:1 in N-methylpyrrolidone solvent system by sufficient stirring to form a positive electrode slurry, which was then applied onto an Al foil by extrusion coating or transfer coating, baked, and cold pressed to obtain a positive electrode plate, on which the thickness of the positive electrode film layer was 218 μm.
[0089] The negative electrode active material, artificial graphite (purchased from BTR New Material), the conductive agent, SP carbon black (from TIMCAL), and the binder, polyvinylidene fluoride (PVDF), were thoroughly mixed in a deionized water solvent system with a weight ratio of 97:2:1 to make a homogeneous mixture, and then coated on a Cu foil, baked, and cold pressed to obtain a negative electrode plate, on which the thickness of the negative electrode film layer was 161 μm.
[0090] A PE porous polymer film was used as the separator.
[0091] The positive electrode plate, separator, and negative electrode plate were wound up in that order according to size to produce a cell, which was then subjected to processes such as packaging, electrolyte injection, chemical formation, and evacuation to obtain a lithium-ion battery.
[0092] Examples 1 to 53: The additives shown in Table 1 were added to the positive electrode slurry, and a cell was produced according to the above-mentioned cell production process.
[0093] The solvated segments are respectively as follows: The segments shown in Equation 1: TIFF2025511549000008.tif52130. The segment shown in Equation 2: TIFF2025511549000009.tif5285, R5 is butylidene. The segment shown in Equation 3: TIFF2025511549000010.tif50151.
[0094] Synthesis Example 1 Synthesis of additives in which the anchor group is a phosphate group, the solvation segment is a segment shown in formula 1, and the terminal group is a styryl group in Examples 1 to 8, 39, and 40 Butanol was weighed and placed in a dry three-neck flask, stirred uniformly at 0°C, phosphorus trichloride was slowly added dropwise, and the temperature was controlled to 0-5°C or less until the reaction was completed. The reaction was then continued at a low temperature for 2 hours, and the temperature was raised to room temperature and the reaction was continued for another 2 hours. After that, the solvent impurities were centrifuged, and the dibutyl phosphite fraction was collected at 66-67°C by vacuum distillation.
[0095] Sulfuryl chloride was added to a dried three-neck flask, the temperature was controlled at about 25°C, and dibutyl phosphite was slowly added dropwise to the flask while stirring uniformly. After the addition was completed, the reaction was continued for another 2 hours at room temperature. The impurities were centrifuged at a low temperature of 35°C, and finally the dibutyl chlorophosphate fraction was collected at 96-98°C by vacuum distillation.
[0096] Add ethylenediamine and distilled water in a ratio of 5:1 into a four-neck flask, add ethylene oxide dropwise at room temperature, then add 50% alkaline solution dropwise, stir for 1 hour, dehydrate under reduced pressure, obtain a white viscous substance, transfer to a polymerization vessel, introduce nitrogen gas to replace, stir and heat, make the pressure ≦ 0.6 Pa, control the temperature at 120 ~ 160 ° C, add epoxypropane (weight ratio with the white viscous substance is 3: 1), react completely, and discharge at room temperature to obtain a pale yellow oily polyether.
[0097] The polyether produced in the above process was added to the reactor and thoroughly stirred. At a temperature of 40-60°C, dibutyl chlorophosphate and polyether were gradually added to the reactor in a molar ratio of 2.5:1. The temperature was raised to 70-80°C, and the reaction time was set to 5-6 hours to obtain an intermediate.
[0098] The intermediate and styrene were dissolved in acetonitrile, a catalytic amount of azodiisobutyronitrile (AIBN) initiator was added, and the mixture was stirred uniformly at room temperature, and the reaction temperature was raised to 75-80°C to polymerize the mixture. After the polymerization reaction was completed, the product was vacuum dried to obtain a copolymer.
[0099] Synthesis Example 2 Synthesis of additives in which the anchor group is a phosphate group, the solvation segment is a segment shown in formula 2, and the terminal group is a styryl group in Examples 9 to 13: Ethylenediamine and distilled water are added in a four-neck flask in a ratio of 5:1, epoxybutane is added dropwise at room temperature, then 50% alkaline solution is added dropwise, stirred for 1 hour, dehydrated under reduced pressure, and a white viscous substance is obtained. The mixture is transferred to a polymerization vessel, and nitrogen gas is introduced to replace the mixture. The mixture is stirred and heated to a pressure of ≦0.6 Pa and the temperature is controlled at 120-160°C. After the reaction is complete, the mixture is discharged at room temperature to obtain a pale yellow oily polyether.
[0100] The polyether produced in the above process was added to the reactor and thoroughly stirred. At a temperature of 40-60°C, dibutyl chlorophosphate and polyether were gradually added to the reactor in a molar ratio of 2.5:1. The temperature was raised to 70-80°C, and the reaction time was set to 5-6 hours to obtain an intermediate.
[0101] The intermediate and styrene were dissolved in acetonitrile, a catalytic amount of azodiisobutyronitrile (AIBN) initiator was added, and the mixture was stirred uniformly at room temperature, and the reaction temperature was raised to 75-80°C to polymerize the mixture. After the polymerization reaction was completed, the product was vacuum dried to obtain a copolymer.
[0102] Synthesis Example 3 Synthesis of additives in which the anchor group is a phosphate group, the solvation segment is a segment shown in formula 3, and the terminal group is a styryl group in Examples 14 to 20: Alkylphenol ethoxylate and dibutyl chlorophosphate were reacted at 70-80°C for 5-6 hours to obtain an intermediate.
[0103] The intermediate and styrene were dissolved in acetonitrile, a catalytic amount of azodiisobutyronitrile (AIBN) initiator was added, and the mixture was stirred uniformly at room temperature, and the reaction temperature was raised to 75-80°C to polymerize the mixture. After the polymerization reaction was completed, the product was vacuum dried to obtain a copolymer.
[0104] The n and b values were adjusted by selecting alkylphenol ethoxylates of corresponding molecular weights, and the molar ratios of anchor groups, solvation segments, and end groups were adjusted by adjusting the dosages of phosphorylating reagent, alkylphenol ethoxylate, and styrene.
[0105] Synthesis Example 4 Synthesis of additives in which the anchor group is a sulfonic acid group, the solvation segment is a segment shown in formula 1, and the terminal group is a styryl group in Examples 21 to 23: The polyether obtained in Synthesis Example 1 was reacted with vinyl sulfonic acid using a strong acid as a catalyst at a reaction temperature of 60 to 70°C for a reaction time of 5 to 6 hours, and then neutralized and polymerized with styrene at 75 to 80°C to obtain the additive.
[0106] Synthesis Example 5 Synthesis of additives in which the anchor group is a sulfonic acid group, the solvation segment is a segment shown in formula 2, and the terminal group is a styryl group in Examples 24 to 26: The polyether obtained in Synthesis Example 2 was reacted with vinyl sulfonic acid using a strong acid as a catalyst at a reaction temperature of 60 to 70°C for a reaction time of 5 to 6 hours, and then neutralized and polymerized with styrene at 75 to 80°C to obtain the additive.
[0107] Synthesis Example 6 Synthesis of additives in which the anchor group is a sulfonic acid group, the solvation segment is a segment shown in formula 3, and the terminal group is a styryl group in Examples 27 to 29: The alkylphenol ethoxylate and vinyl sulfonic acid were reacted using a strong acid as a catalyst at a reaction temperature of 60 to 70°C for a reaction time of 5 to 6 hours, and then the reaction mixture was neutralized and polymerized with styrene at 75 to 80°C to obtain the above additive.
[0108] Synthesis Example 7 Synthesis of additives in which the anchor group is a carboxylic acid group, the solvation segment is a segment shown in formula 1, and the terminal group is a styryl group in Examples 30 to 32, 48, and 49: The polyether obtained in Synthesis Example 1 was subjected to esterification synthesis with an unsaturated carboxylic acid (e.g., acrylic acid, methacrylic acid, etc., selected according to the target additive), using a strong acid as a catalyst, at a reaction temperature of 45 to 60°C, for a reaction time of 3 to 4 hours, and then polymerized with styrene to obtain the above-mentioned additive.
[0109] Synthesis Example 8 Synthesis of additives in which the anchor group is a carboxylic acid group, the solvation segment is a segment shown in formula 2, and the terminal group is a styryl group in Examples 33 to 35: The polyether obtained in Synthesis Example 2 was subjected to esterification synthesis with an unsaturated carboxylic acid (e.g., acrylic acid, methacrylic acid, etc., selected according to the target additive), using a strong acid as a catalyst, at a reaction temperature of 45 to 60°C, for a reaction time of 3 to 4 hours, and then polymerized with styrene to obtain the above-mentioned additive.
[0110] Synthesis Example 9 Synthesis of additives in which the anchor group is a carboxylic acid group, the solvation segment is a segment shown in formula 3, and the terminal group is a styryl group in Examples 36 to 38: The alkylphenol ethoxylate and unsaturated carboxylic acid (e.g., acrylic acid, methacrylic acid, etc., selected according to the target additive) were esterified using a strong acid as a catalyst at a reaction temperature of 45-60°C for a reaction time of 3-4 h, and then polymerized with styrene to obtain the above additive.
[0111] Synthesis Example 10 In Example 41, synthesis of an additive in which the anchor group is a phosphate group, the solvation segment is a segment shown in Formula 1, and the terminal group is a butyl group: The intermediate obtained in Synthesis Example 1 and butene were polymerized at 70 to 75° C. to obtain the above additive, and AIBN (azodiisobutyronitrile) was used as an initiator.
[0112] Synthesis Example 11 Synthesis of amide-type polyether of Comparative Example 2 (anchor group is an amide group, solvation segment is a segment shown in formula 1, and terminal group is a styryl group): The polyether obtained in Synthesis Example 1 was added to the reaction vessel and thoroughly stirred. At a temperature of 40°C to 60°C, butenamide and polyether were gradually added to the reaction vessel in a molar ratio of 2.5:1. The temperature was raised to 70°C to 80°C, and the reaction time was set to 5 to 6 hours to obtain an intermediate.
[0113] The intermediate and styrene were dissolved in acetonitrile, a catalytic amount of azodiisobutyronitrile (AIBN) initiator was added, and the mixture was stirred uniformly at room temperature, and the reaction temperature was raised to 75-80°C to polymerize the mixture. After the polymerization reaction was completed, the product was vacuum dried to obtain a copolymer.
[0114] Synthesis Example 12 Polyacrylamide of Comparative Example 3 An aqueous solution of AM (w=20%) was added to a four-neck flask, N2 was introduced to replace the atmosphere, and the mixture was stirred and heated to 50-80°C. An initiator (NH4)2S2O8 / NaHSO3) was added in a 1:1 ratio, and at the same time, a chain transfer agent such as mercaptoethanol was added, and the temperature was maintained constant. The mixture was stirred for 5-6 hours to stop the reaction, and then added to anhydrous ethanol in a 1:4 ratio to precipitate a white precipitate. After suction filtration, the material was vacuumed to -0.1Mpa and dried at a temperature of 40°C for 24 hours until a constant weight was obtained, obtaining the desired material.
[0115] The structures of each of the above synthesis products were characterized by infrared and proved to be the target compounds.
[0116] [Table 1] TIFF2025511549000012.tif255168TIFF2025511549000013.tif254166
[0117] Test Method 1) Solid content Place the moisture meter on the designated operating table, adjust the bracket so that the horizontal bubble is in the center and the moisture meter is in a horizontal state, open the top cover of the instrument, put it into the aluminum tray, click the control panel to clear, add 5-8g of slurry, and close the top cover. Set the temperature of the moisture meter to 120°C, and the test shows that the weight percentage after completion is the consumed moisture, and 100%-consumed moisture=solid content.
[0118] 2) Viscosity of the positive electrode slurry Take a 500ml beaker to take a sample from the stirring tank immediately after stirring, select a 62# rotor, set the water bath temperature to 45℃, set the speed to 12RPM, rotate the viscometer up-down button, slowly lower it, avoiding the inclusion of air bubbles, immerse the rotor in the slurry from the center position of the beaker until it sinks into the rotor groove, press the motor start key, start measuring and timing, read the relatively stable data within 3~6min, this data is the viscosity value of the measured sample.
[0119] 3) Gelation state after leaving it for 12 hours Prepare 500 ml of fresh slurry, seal the fresh slurry in the beaker with plastic wrap, place in a metal cabinet, and leave to stand for 12 hours. Open the wrap and gently move the surface of the slurry with a steel ruler to check the condition of the slurry.
[0120] The gel state is classified into the following grades. (1) Slight gelation: The slurry has high fluidity, but reflections on the liquid surface are evident and flow lines of the slurry protrude above the liquid surface. (2) Moderate gelation: The slurry has low fluidity and exhibits flocculence; the slurry resembles the flocculent type, but has no solid properties and no jelly mass. (3) Severe gelation: The slurry has no flowability and is gel-like; the slurry exhibits solid properties, has no flowability, and can be lifted as a whole.
[0121] 4) Coating cracking condition For coating, an 18m oven is used, the speed is set at 6m / min, and the appearance of the coating is observed to see whether there are any visible cracks.
[0122] 5) Plate brittleness test: Take a non-thinned plate without defects and cut it into samples with length*width 20cm*2.5cm along the longitudinal direction, the number of samples is ≧8, first pre-fold it, then place the film piece on the test table and roll it once with a 2kg cylindrical roller. If the light is transmitted, the brittle light transmission number is 1. If the light is not transmitted, repeat the folding and rolling in the reverse direction. Hold the fold line up to the light and observe whether the light is transmitted or broken, and record the actual number of folding times. The more the number of folding times, the stronger the flexibility and the lower the brittleness of the plate are characterized.
[0123] 6) Positive electrode film resistance Film resistance: Take a cold-pressed sample with an area of 4cm*25cm.
[0124] Select the resistance meter BER1100 manufactured by Xiamen Yuan Neng Technology Co., Ltd., set it to single point mode, and the test area of the input terminal is 154.02 mm 2 The number of parallel samples is 20, the pressure is 0.4t, and the time interval is t=15s. The current collector of the test plate is placed in the center of the probe, and the run button in the software is clicked first, and then the reversing valve is moved down, and data is automatically collected after 15s.
[0125] 7) Initial efficiency After standing for 5 min, the battery was formed by constant current charging at a current density of 0.02C for 10 h, i.e., C0; after standing for 5 min, the battery was charged at a constant current of 0.5C to 3.65V, i.e., C1; after standing for 5 min, the battery was discharged at a current density of 0.5C to 2.5V, i.e., D0; and the initial efficiency=D0 / (C1+C0).
[0126] 8) Cycle capacity retention test The secondary battery thus prepared was placed in a NEWARE device and charged at a constant current of 0.33C at a temperature of 45°C, then charged at a constant voltage to the rated voltage. After leaving the battery to stand for 10 minutes, it was discharged at a constant current of 0.33C to the cut-off voltage, and the discharge capacity at this time was recorded. The battery was then left to stand for another 10 minutes. This cycle was repeated for 300 times and the capacity retention rate was calculated as follows: (300th cycle capacity / 1st cycle capacity)*100%.
[0127] [Table 2] TIFF2025511549000015.tif102170
[0128] The solid content, viscosity, gelation state after standing for 12 hours, brittleness of the plate, and film resistance in the above table are classified as processing performance of the plate, and the initial efficiency and capacity retention rate (%) at 300 cycles are classified as electrical performance. The following can be seen from the data in the above table. 1) Compared with Comparative Example 1 in which no relevant additive was added, Examples 1 to 51 show that the addition of the additives of the present application significantly improves both the processing performance and electrical performance of the cell. 2) Compared to the polyacrylamide of Comparative Example 2, Examples 1 to 51 show that the addition of the additive of the present invention results in excellent cell processing performance and electrical performance. 3) Compared with Comparative Example 3, Examples 1 to 51 show that when too much of the additive of the present invention is added, the processing performance is excellent, but the electrical performance is deteriorated. 4) Comparing Examples 40 and 1 to 39, if only the non-polar second group is selected as the anchor group, only the non-polar portion is fixed, the dispersion effect is weakened, the membrane resistance is increased, and the electrical performance is somewhat low. 5) By comparing Examples 1, 7 and 8, Examples 9, 12 and 13, and Examples 14, 19 and 20, it can be seen that when the composition of the additive is changed, the viscosity of the positive electrode slurry containing the additive is changed, which further affects the gelling state and coating cracking state of the positive electrode slurry.
[0129] Although the present application has been described with reference to the preferred embodiments, various modifications can be made thereto and equivalents can be substituted for the elements therein without departing from the scope of the present application. In particular, each technical feature mentioned in each embodiment can be combined in any manner unless there is a conflict in structure. The present application is not limited to the specific embodiments disclosed in the specification, but includes all technical solutions within the scope of the claims. [Explanation of symbols]
[0130] 1 Battery pack 2 Upper Box 3 Lower Box 4 Battery Module 5 Secondary battery 51 Housing 52 Electrode assembly 53 Top cover assembly
Claims
1. -COOR 1 , -SO 3 R 2 and -PO(OR 3 ) OR 4 A polymer comprising an anchor group, a solvating segment and an end group selected from any one or more of: R 1 , R 2 , R 3 and R 4 each independently comprises a first group and a second group, the first group being H and the second group being C 1 ~C 12 Alkyl group, C 6 ~C 20 Aryl groups and C 5 ~C 20 heteroaryl groups; The solvation segment is 、 、 Any one or more of the segments consisting of the following structural units are selected: The R 5 is C 1 ~C 6 alkylene groups, A polymer in which 30≦a≦60, 1≦n≦10, 1≦b≦8, 0≦c≦20, and 8≦d≦60.
2. The molar ratio of the anchor group to the solvation segment to the end group is (1-1.5):(8-8.8):(0.2-0.5), and optionally the second group is 1 ~C 6 Alkyl group and C 6 ~C 12 aryl groups, optionally where 30≦a≦40, 4≦n≦8, 4≦b≦8, 10≦c≦20, 40≦d≦60.
3. 3. The polymer according to claim 1, wherein the molar ratio of the first groups to the second groups is from 2:8 to 8:
2.
4. The terminal group is C 1 ~C 12 Alkyl group, C 1 ~C 12 Alkoxy group and C 6 ~C 20 aryl groups, optionally the terminal group is selected from any one or more of 1 ~C 6 Alkyl group, C 1 ~C 6 Alkoxy group and C 6 ~C 12 4. The polymer of claim 1, wherein the aryl group is selected from any one or more of the following:
5. The polymer according to any one of claims 1 to 4, wherein the weight average molecular weight of the polymer is from 500 to 20,000, optionally from 10,000 to 10,000.
6. A positive electrode material composition comprising a positive electrode active material, a conductive agent, and an additive which is the polymer according to any one of claims 1 to 5.
7. 7. The positive electrode material composition according to claim 6, wherein the weight content of said additive in said positive electrode material composition is 0.01% to 3%, and optionally 0.2% to 0.5%.
8. The weight content of the positive electrode active material in the positive electrode material composition is 94% to 99%, and optionally the positive electrode active material includes any one or more of the group consisting of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, magnesium-rich lithium nickel cobalt manganese oxide, lithium manganese spinel, and lithium nickel manganese spinel, and optionally the D of the positive electrode active material. V50 8. The positive electrode material composition according to claim 6, wherein the particle size is 0.8 μm to 2.5 μm.
9. The positive electrode material composition according to any one of claims 6 to 8, wherein the weight content of the conductive agent in the positive electrode material composition is 0.3% to 3%, and optionally, the conductive agent includes one or more of the group consisting of conductive carbon black, conductive graphite, metal particles, carbon nanotubes, carbon fibers, graphene, and conductive polymers.
10. The positive electrode material composition according to any one of claims 6 to 9, further comprising a binder, and optionally a weight content of the binder in the positive electrode material composition is 0.5% to 3%, and optionally the binder comprises one or more of the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, vinylidene fluoride-trifluorochloroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, and vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer.
11. A positive electrode slurry comprising a solvent and the positive electrode material composition according to any one of claims 6 to 10.
12. The positive electrode slurry according to claim 11, wherein the positive electrode slurry has a viscosity of 4000 to 30000 mPa·s.
13. A positive electrode plate comprising a current collector and a positive electrode film layer comprising the positive electrode material composition according to any one of claims 6 to 10 or obtained by drying the positive electrode slurry according to claim 11 or 12.
14. A secondary battery comprising the positive electrode plate according to claim 13, a separator, and a negative electrode plate.
15. A power consuming device comprising a secondary battery or a battery module or a battery pack selected from the secondary battery of claim 14.
Citation Information
Patent Citations
Viscosity-improving agent
JP2009114350A
Polymer electrolyte and method for producing same
JP2020510983A
Polyisocyanate composition, block polyisocyanate composition, coating composition, aqueous coating composition, and coating base material
WO2018056408A1